IMPROVING THE METHODOLOGY OF TEACHING ENGLISH USING ELEMENTS OF DISTANCE LEARNING - Qodirqulova Munisa (TADQIQOTLAR, 2026)
This article is dedicated to enhancing the methodology of teaching English through the integration of distance learning elements. It explores the application of distance learning technologies in the teaching process, the development of students’ independent working skills, and the creation of an interactive learning environment. The article discusses the advantages of distance learning, the integration of modern platforms into the educational process, and offers recommendations for educators. The ultimate goal is to make the process of learning English more effective by improving teaching methodologies.